Nickel electroplating composition for crude nickel
Patent Information
- Application Number
- JP2023156286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-26
- Filing Date
- 2023-09-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-09-21
Smart Images

Figure 0007634622000026 
Figure 0007634622000027 
Figure 0007634622000001
Abstract
Description
[Technical field]
[0001] The present invention relates to nickel electroplating compositions for depositing crude nickel on a substrate. More specifically, the present invention relates to nickel electroplating compositions for depositing crude nickel on a substrate, the nickel electroplating compositions comprising a mercaptotetrazole. [Background technology]
[0002] Leadframes are used in the manufacture of semiconductor devices to mount and process semiconductor dice or chips. The leadframe serves to electrically connect the chip to an external device via the leads of the leadframe. Examples of leadframes include spot silver and solder coated leadframes, and palladium preplated leadframes (PPF).
[0003] PPF is a three-layer leadframe containing nickel with a thickness range of 0.5-2 μm, palladium with a thickness range of 10-100 nm, and gold with a thickness range of 3-9 nm. The nickel layer is used as an underlayer to prevent copper diffusion from the leadframe bulk into the palladium layer and to bond with solder. The palladium layer functions to prevent oxidation of the nickel surface and diffusion of gold into the nickel layer, while the top gold flash layer is designed to prevent oxidation of palladium and outgassing absorbed by palladium.
[0004] Semiconductor chips are mounted on lead frames and bond wire connections are made between the semiconductor chips and the lead frames. Each semiconductor chip is protected from the environment by encapsulating it with a plastic molding compound, also called epoxy molding compound (EMC). Good adhesion between the lead frame and the EMC is very important to ensure high reliability and proper functioning of the interconnect circuit (IC) devices. Poor adhesion can lead to delamination, cracking and the "popcorn" phenomenon. This results in failure of the device, especially under harsh conditions such as high temperature, high humidity and thermal cycling.
[0005] There are various methods in the art to avoid the delamination of epoxy molding compound from the lead frame or substrate. These methods include using special lead frame designs, chemical bonding, and mechanical interlocks. Special lead frame designs include holes, grooves, and hemispheres created mechanically or by laser machining on the lead frame surface. These methods may not be reliable enough to achieve industry standards for adhesion between the EMC and the lead frame or may not meet MSL-1 compliance (Moisture Resistance Level-1, 168 hours at 85°C and 85% relative humidity, IPC / JEDECJ-STD-20).
[0006] Chemical adhesion techniques include brown oxide, organic adhesion promoters, polymer primers and coupling agents. The mechanism is that brown oxide and organic adhesives have one or two functional groups that link with EMC and leadframe. Thus, adhesion is enhanced by chemical bonding. In the brown oxide method, the copper on the substrate surface is oxidized to copper oxide or cuprous oxide. However, the brown oxide method is not applicable to Ni / Pd / Au pre-plated leadframes because the copper surface is not exposed. Moreover, the micro-etching effect in the brown oxide process can weaken the strength of the leadframe and cause dimensional variations.
[0007] Organic treatments have some limitations that prevent their widespread use in mass production. For example, there can be compatibility problems between organic adhesion promoters and various types of EMC. With regard to the polymer primer, process steps can be complicated. Copper coupling agents can undergo hydrolysis under normal packaging conditions.
[0008] The gold and palladium layers of PPF (Ni / Pd / Au) leadframes are essentially inert metals, so it is difficult to modify the chemical bonds to improve die adhesion. The only feasible way is to use the mechanical interlocking effect by roughening the surface of the copper or nickel substrate. The palladium and gold layers are too thin to be roughened in the manufacturing process.
[0009] US Pat. No. 5,399,433 and US Pat. No. 5,499,463 disclose nickel plating baths for depositing a crude nickel layer to improve adhesion between the nickel layer and a resin sealing of a semiconductor package. US Pat. No. 5,499,433 discloses a nickel plating bath of nickel chloride, sodium thiocyanate and ammonium chloride to provide a crude nickel deposit. US Pat. No. 5,499,433 discloses a nickel plating bath containing nickel sulfate, ammonium sulfate, sodium sulfate, sodium chloride and boric acid to deposit a crude nickel layer. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] U.S. Patent No. 7,190,057 [Patent Document 2] U.S. Patent No. 7,285,845 Summary of the Invention [Problem to be solved by the invention]
[0011] Although nickel plating baths exist that deposit crude nickel, a need remains for improved nickel electroplating baths that enable the deposition of crude nickel. [Means for solving the problem]
[0012] The present invention relates to a compound comprising nickel ions and the following formula: [ka] (wherein R1 is selected from hydrogen, linear or branched (C1-C6) alkyl, linear or branched hydroxy(C1-C6) alkyl or a salt thereof, linear or branched carboxy(C1-C6) alkyl or a salt thereof, linear or branched sulfo(C1-C6) alkyl or a salt thereof, linear or branched amino(C1-C6) alkyl, phenyl or benzyl; and X + is H + or an alkali metal ion).
[0013] The present invention also provides a) providing a substrate; b) nickel ions and the formula: [ka] (wherein R1 is selected from hydrogen, linear or branched (C1-C6) alkyl, linear or branched hydroxy(C1-C6) alkyl or a salt thereof, linear or branched carboxy(C1-C6) alkyl or a salt thereof, linear or branched sulfo(C1-C6) alkyl or a salt thereof, linear or branched amino(C1-C6) alkyl, phenyl, or benzyl; and X + is H + contacting the substrate with a nickel electroplating composition comprising a mercaptotetrazole having a mercapto group having an ion, wherein the ion is an alkali metal ion; and c) depositing a nickel layer on the substrate, the nickel layer having Sa≧70 nm and Sdr≧4%; The present invention also relates to a method for electroplating nickel metal onto a substrate, comprising:
[0014] The nickel electroplating compositions of the present invention allow for the deposition of a rough nickel layer having a substantially particulate or mound-type morphology and protuberances that improve adhesion between the rough nickel layer and adjacent metal layers and improve mold adhesion between epoxy molding compounds such as those found in lead frames. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is an SEM at 10,000 times of a conventional nickel layer having a substantially smooth surface. [Diagram 2] FIG. 2 is an SEM at 10,000x of a crude nickel layer electroplated from a nickel bath of the present invention, showing the mound-shaped morphology and protrusions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The abbreviations used throughout this specification have the following meanings, unless the context clearly indicates otherwise: °C = degrees Celsius; g = grams; Kg = kilogram; L = liter; mL = milliliter; m = meter; cm = centimeter; μm = microns; nm = nanometer; DI = deionized; A = amperes; ASD = amperes / dm 2 = current density or plating rate; PPF = palladium pre-plated lead frame, EMC = epoxy molding compound, XRF = x-ray fluorescence, AFM = atomic force microscope, KV = kilovolts, V = volts, LPM = liters per minute; min = minutes; MSL = moisture resistance level; MSL-1 = moisture resistance level-1, 168 hours at 85°C and 85% relative humidity; w / o MSL-1 = no MSL treatment; w / MSL-1 = with MSL treatment; H = hydrogen; H + = hydrogen ion; N = nitrogen; O = oxygen; S = sulfur; C = carbon; Ni = nickel; Pd = palladium; Au = gold; Na + = sodium cation; K + = potassium cation; and wt% = weight percent.
[0017] The term "moiety" refers to one or more atoms that make up a part of a molecule. The term "adjacent" refers to two metal layers in direct contact such that they have a common interface. The term "aqueous" refers to water or water-based. The term "matte" refers to a dull appearance. The terms "composition" and "bath" are used interchangeably throughout this specification. The term "Ra" refers to the arithmetic mean deviation of profile roughness. The term "Sa" refers to the arithmetic mean height within the evaluation area and is substantially equivalent to Ra, but Sa provides more stable results since this parameter is not as susceptible to scratches, contamination and measurement noise. The term "Sdr" refers to the developed interface area ratio corresponding to the surface area ratio with a correlation of Sdr = (surface area ratio - 1) x 100%. The terms "electroplating", "plating" and "deposition" are used interchangeably throughout this specification. The term "morphology" refers to the shape, size, texture or topography of a surface or article. The term "ion" refers to a cation or anion depending on the context in which it is used herein and as would be understood by one of ordinary skill in the art. The term "IPC / JEDECJ-STD-20" refers to the Institute for Interconnecting and Packaging Electronic Circuits (IPC) and the Solid State Technology Association for Standard Classification of Moisture Sensitivity Levels (MSL) for Leadframe Integrated Circuit Devices. The terms "a" and "an" may refer to both the singular and the plural throughout this specification. All numerical ranges are inclusive and combinable in any order, except where it is logical that such numerical ranges are constrained to add up to 100%.
[0018] The present invention relates to a compound having the following chemical structure: [ka] (wherein R1 is selected from hydrogen, linear or branched (C1-C6) alkyl, linear or branched hydroxy(C1-C6) alkyl or a salt thereof, linear or branched carboxy(C1-C6) alkyl or a salt thereof, linear or branched sulfo(C1-C6) alkyl or a salt thereof, linear or branched amino(C1-C6) alkyl, phenyl or benzyl; and X + is H + or an alkali metal ion).
[0019] Preferably, R1 is selected from hydrogen, linear or branched (C1-C6) alkyl, linear or branched hydroxy(C1-C6) alkyl or a salt thereof, linear or branched carboxy(C1-C6) alkyl or a salt thereof, linear or branched sulfo(C1-C6) alkyl or a salt thereof, and X + is H + , or Na + and K + The alkali metal ion is selected from the group consisting of:
[0020] More preferably, R1 is selected from hydrogen, linear or branched (C1-C3) alkyl, linear or branched hydroxy(C1-C3) alkyl or a salt thereof, linear or branched carboxy(C1-C3) alkyl or a salt thereof, linear or branched sulfo(C1-C3) alkyl or a salt thereof, and X + H + Or Na + It is.
[0021] More preferably, R1 is selected from hydrogen, (C1-C2)alkyl, hydroxy(C1-C2)alkyl or a salt thereof, carboxy(C1-C2)alkyl or a salt thereof, sulfo(C1-C2)alkyl or a salt thereof, and X + H + Or Na + It is.
[0022] The most preferred mercaptotetrazoles have the formula: [ka] 5-Mercapto-(1H)-tetrazolylacetic acid, sodium salt and [ka] 5-Mercapto-1H-tetrazole-1-methanesulfonic acid, disodium salt.
[0023] Salts of hydroxy, carboxy and sulfo moieties include, but are not limited to, preferably alkali metal salts such as sodium salts, potassium salts and lithium salts, more preferably sodium salts and potassium salts, and even more preferably sodium salts.
[0024] Preferably, mercaptotetrazole is included in the nickel electroplating composition in an amount of 5 ppm or more, more preferably 10 ppm to 100 ppm, even more preferably 20 ppm to 80 ppm, even more preferably 30 ppm to 60 ppm, and most preferably 45 ppm to 55 ppm.
[0025] The nickel electroplating composition includes nickel ions from one or more sources of water-soluble nickel salts, including, but not limited to, nickel sulfate and its hydrates, nickel sulfate hexahydrate and nickel sulfate heptahydrate, nickel sulfamate and its hydrate, nickel sulfamate tetrahydrate, nickel chloride and its hydrate, nickel chloride hexahydrate, nickel carbonate, nickel methanesulfonate, nickel bromide, nickel fluoride, nickel iodide, nickel oxalate, nickel citrate, nickel tetrafluoroborate, nickel hypophosphite, and nickel acetate. Preferably, the source of nickel ions is nickel sulfamate, nickel chloride, or mixtures thereof.
[0026] The one or more nickel ion sources are included in the aqueous nickel electroplating composition in an amount sufficient to provide a desired nickel ion concentration to achieve a desired crude nickel deposit. Preferably, the concentration of the nickel salt in the nickel electroplating composition of the present invention is 20 g / L or more. More preferably, the concentration of the nickel salt is in the range of 25 g / L to 750 g / L, even more preferably, the concentration of the nickel salt is in the range of 30 g / L to 500 g / L, and most preferably, the concentration of the nickel salt is in the range of 30 g / L to 300 g / L.
[0027] Chloride ions may optionally be included in the aqueous nickel electroplating compositions of the present invention. One or more sources of chloride ions are preferably included in an amount of from 0 g / L to 50 g / L, more preferably from 0 g / L to 30 g / L, even more preferably from 0 g / L to 20 g / L, and most preferably from 3 g / L to 10 g / L.
[0028] Sources of chloride ions include, but are not limited to, nickel chloride, nickel chloride hexahydrate, hydrogen chloride, alkali metal salts such as sodium chloride and potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, organic hydrochlorides such as, but not limited to, guanidine hydrochloride, ethylenediamine dihydrochloride, trimethylammonium chloride, pyridine hydrochloride, phenylammonium chloride, and hydrazine dihydrochloride. Preferably, the sources of chloride ions are nickel chloride and nickel chloride hexahydrate.
[0029] The nickel electroplating composition of the present invention is acidic. The pH is preferably in the range of 2 to 6, more preferably 2.5 to 4.5, and even more preferably 3 to 4.2. Inorganic acids, organic acids, inorganic bases, organic bases, and salts thereof can be used to adjust the pH of the aqueous nickel electroplating composition. Such acids include, but are not limited to, inorganic acids such as sulfuric acid, hydrochloric acid, sulfamic acid, boric acid, and salts thereof. Organic acids include, but are not limited to, organic acids such as acetic acid, aminoacetic acid, ascorbic acid, lactic acid, 5-sulfosalicylic acid, and salts thereof. Inorganic bases such as sodium hydroxide and potassium hydroxide, as well as organic bases such as various amines and ammonium acetate, can also be used to adjust the pH. Preferably, the pH adjuster is selected from boric acid, lactic acid, 5-sulfosalicylic acid, and ammonium acetate. Most preferably, the pH adjuster is boric acid, its salts, and ammonium acetate. The pH adjuster can be added in an amount required to maintain the desired pH range.
[0030] Optionally, one or more surfactants can be included in the aqueous nickel electroplating compositions of the present invention. Such surfactants include, but are not limited to, ionic surfactants, such as cationic and anionic surfactants, nonionic surfactants, and amphoteric surfactants. Preferably, the surfactants can be used in conventional amounts, such as 0.05 g / L to 150 g / L, more preferably 0.05 g / L to 15 g / L, and even more preferably 0.05 g / L to 5 g / L.
[0031] Examples of surfactants include, but are not limited to, anionic surfactants such as sodium di(1,3-dimethylbutyl)sulfosuccinate, sodium 2-ethylhexyl sulfate, sodium diamylsulfosuccinate, sodium lauryl sulfate, sodium lauryl ether sulfate, sodium dialkylsulfosuccinate, and sodium dodecylbenzenesulfonate, and cationic surfactants such as quaternary ammonium salts such as perfluorinated quaternary amines. An example of a commercially available anionic surfactant is AEROSOL-M-80 dihexylsulfosuccinate sodium salt available from Solvay Chemicals.
[0032] The aqueous nickel electroplating compositions of the present invention preferably do not contain alloying metals or metals that may be included in metal plating baths to increase or improve the brightness of the nickel metal deposit.
[0033] Additionally, the aqueous nickel electroplating compositions of the present invention are preferably cyanide and cyanide compounds free.
[0034] Preferably, the aqueous nickel electroplating compositions of the present invention comprise nickel cations and corresponding counter anions from one or more nickel salts, of the formula: [ka] (wherein R1 is selected from hydrogen, linear or branched (C1-C6) alkyl, linear or branched hydroxy(C1-C6) alkyl or a salt thereof, linear or branched carboxy(C1-C6) alkyl or a salt thereof, linear or branched sulfo(C1-C6) alkyl or a salt thereof, and X + is H + , or Na + and K +(wherein the anion is an alkali metal ion selected from the group consisting of), optionally a chloride anion and corresponding countercation from one or more chloride salts, optionally one or more pH adjusters, optionally one or more surfactants, and water.
[0035] More preferably, the aqueous nickel electroplating compositions of the present invention comprise nickel cations and corresponding counter anions from one or more nickel salts, Mercaptotetrazoles having the formula: [ka] (wherein R1 is selected from hydrogen, linear or branched (C1-C3) alkyl, linear or branched hydroxy(C1-C3) alkyl or a salt thereof, linear or branched carboxy(C1-C3) alkyl or a salt thereof, linear or branched sulfo(C1-C3) alkyl or a salt thereof, and X + is H + , or Na + wherein R is an integer from 1 to 3; optionally a chloride anion and corresponding countercation from one or more chloride salts; one or more pH adjusters; optionally one or more surfactants; and water.
[0036] More preferably, the aqueous nickel electroplating compositions of the present invention are comprised of a nickel cation from a nickel salt selected from the group consisting of nickel chloride, nickel sulfamate, nickel sulfate, and mixtures thereof, and a corresponding counter anion, mercaptotetrazole having the formula: [ka] (wherein R1 is selected from hydrogen, (C1-C2) alkyl, hydroxy(C1-C2) alkyl or a salt thereof, carboxy(C1-C2) alkyl or a salt thereof, sulfo(C1-C2) alkyl or a salt thereof, and X+ is H + , or Na + (wherein n is an integer from 1 to 3), optionally a chloride anion and corresponding countercation from one or more chloride salts selected from the group consisting of nickel chloride and sodium chloride, a pH adjuster selected from the group consisting of boric acid, lactic acid, 5-sulfosalicylic acid, salts thereof, ammonium acetate, and mixtures thereof, one or more surfactants, and water.
[0037] A method of electroplating crude nickel includes providing an aqueous nickel electroplating composition and contacting a substrate with the aqueous nickel electroplating composition, such as by immersing the substrate in the composition or spraying the substrate with the composition. A current is applied using a conventional rectifier in which the substrate acts as the cathode and a counter electrode or anode is present. The anode can be any conventional soluble or insoluble anode used to electroplate nickel metal adjacent to a surface of a substrate. The aqueous nickel electroplating composition of the present invention deposits a nickel metal layer having a rough, granular or mound-like morphology and having protrusions on the substrate.
[0038] Preferably, the current density is in the range of 1 ASD or more, more preferably, the current density is in the range of 2 ASD to 20 ASD, and even more preferably, the current density is in the range of 5 ASD to 15 ASD.
[0039] The temperature of the nickel electroplating composition for depositing crude nickel is preferably in the range of 30° C. to 70° C., more preferably in the range of 40° C. to 65° C., and even more preferably in the range of 45° C. to 60° C. Preferably, the nickel electroplating composition is under continuous stirring during electroplating.
[0040] The thickness of the crude nickel metal layer can range from 0.5 μm or more. Preferably, the crude nickel layer has a thickness ranging from 0.5 μm to 50 μm, more preferably from 0.5 μm to 10 μm, and even more preferably from 0.5 μm to 5 μm. The thickness of the nickel metal layer can be measured by conventional methods known in the art, such as XRF. For example, the thickness of the nickel layer can be measured using a Bowman Series P X-Ray Fluorimeter (XRF) available from Bowman, Schaumburg, IL. The XRF can be calibrated using a pure nickel thickness standard from Bowman.
[0041] The nickel layer preferably has a coarse grained particle morphology with the particles having a height of 400 nm to 700 nm, preferably a base diameter of 200 nm to 600 nm, more preferably a height of 500 nm to 700 nm and a base diameter of 250 nm to 600 nm. The greater the thickness, the greater the roughness and grain size of the nickel deposit. Such parameters can be measured using an Olympus 3D Laser Microscope-LEXT OLS5000-LAF (available from Olympus Scientific Solutions Americas). Other methods and equipment known to those skilled in the art can also be used.
[0042] Preferably, the nickel layer surface has Sa of 70 nm or more, more preferably Sa of 70 nm to 180 nm, which is substantially equal to Ra. Preferably, Sdr is 4% or more, more preferably Sdr is 4% to 10%, and even more preferably 5% to 10%. Such parameters can be measured using conventional methods known in the art, such as by an Olympus 3D laser microscope or AFM. For example, Sa and Sdr can be measured using an Olympus 3D Laser Microscope-LEXT OLS5000-LAF. Surface roughness can be measured, for example, by scanning a surface area of 256 μm×256 μm at a 50x objective magnification.
[0043] The aqueous nickel electroplating compositions of the present invention can be used to deposit nickel layers on a variety of substrates, both conductive and semiconductive. Preferably, the nickel layer is deposited adjacent to copper, copper alloy, and nickel-iron alloy layers of the substrate. Copper alloys include, but are not limited to, brass, bronze, including cupro-nickel, copper-tin alloys, and copper-bismuth alloys.
[0044] A precious metal is deposited adjacent to the crude nickel layer, preferably such that the crude nickel layer and the precious metal have a common interface. Such precious metals include, but are not limited to, gold and palladium. Preferably, the palladium is deposited adjacent to the crude nickel forming a common interface with the crude nickel, and the gold is deposited adjacent to the palladium such that the gold and palladium have a common interface. Preferably, the palladium layer has a thickness in the range of 5 nm to 20 nm, and preferably, the gold layer has a thickness in the range of 0.5 nm to 5 nm. Such an arrangement of metal layers is called PPF and is common in lead frames. Such a lead frame is encapsulated in an EMC.
[0045] The rough nickel layer improves the bond between a substrate, such as a lead frame, and the EMC. The rough nickel also improves gold wire bonding to the PPF surface. The rough nickel surface increases the contact area between the lead frame and the EMC, and between the lead frame and the bond wire.
[0046] An IC package including the roughened nickel layer of the present invention can be expected to provide good adhesion with epoxy molding compounds, prevent molding compound delamination, and comply with MSL-1 (Moisture Resistance Level-1, 168 hours at 85°C and 85% relative humidity, IPC / JEDEC J-STD-20).
[0047] The following examples are included to further illustrate the invention, but are not intended to limit its scope. EXAMPLES
[0048] Example 1 Hull Cell Test Three aqueous nickel electroplating baths were prepared:
[0049] [Table 1]
[0050] [Table 2]
[0051] [Table 3]
[0052] The Hull Cell tests were conducted using the following operating parameters: applied current 5A, 3 minutes, 55°C, 4 LPM air agitation. Current density ranged from 2 ASD to 20 ASD along the length of the Hull Cell panel. During plating, the bath pH for the nickel bath in Table 1 was 3.56, the nickel bath in Table 2 was 3.36, and the nickel bath in Table 3 was 1.25. The Hull Cell panels were made of bronze (copper-zinc alloy). The panels were first cleaned by electrocleaning at 4-6V, 60°C for 30 seconds using 60 g / L RONACLEAN™ GP-300 (available from DuPont de Nemours, Inc.) electrocleaning solution, and then activated with 100 g / L of pre-dip solution ACTRONAL™ 988 solution (available from DuPont de Nemours, Inc.) for 5 seconds at room temperature. After plating, the panels were rinsed with DI water and air-dried at room temperature. The thickness of each panel was measured by a Bowman Series PX-ray Fluorescence Spectrometer (XRF) at 10 ASD, one of the most common current densities used in actual production line applications. The XRF was calibrated using Bowman pure nickel thickness standards. The thicknesses of the nickel deposits at 10 ASD from the plating baths in Table 1 (invention), Table 2 (invention) and Table 3 (comparison) were 5.66 μm, 5.11 μm and 5.43 μm, respectively.
[0053] The panels plated with the nickel bath of the present invention had a matte appearance at current densities between 2 and 20 ASD. In contrast, the panels plated with the comparative nickel bath had an uneven surface with haze and little reflection at all current densities between 2 and 20 ASD.
[0054] The roughness of the nickel layer of each panel was measured by Olympus 3D Laser Microscope-LEXT OLS5000-LAF. The surface roughness was measured by scanning a surface area of 256 μm×256 μm at 10 ASD points of the Hull Cell panel with a magnification of 50× objective lens. The surface roughness was characterized by area roughness index including Sa (arithmetic mean height) and Sdr (developed interface area ratio). Sa is substantially equal to Ra (arithmetic mean deviation) of profile roughness, and Sdr corresponds to the industrially used surface ratio, with a correlation of Sdr=(surface ratio−1)×100%. The higher Sa or Sdr, the rougher the nickel deposit. The average Sa of the nickel layer plated from the bath of the present invention in Table 1 was 0.1 μm and the average Sdr was 7.41%, and the average Sa of the nickel layer plated from the bath of the present invention in Table 2 was 0.12 μm and the average Sdr was 8.27%. In contrast, the nickel layer plated from the comparative bath had an average Sa of 0.068 μm and an average Sdr of 4.71%. The nickel layer plated from the nickel plating bath of the present invention had a significantly increased surface roughness compared to the nickel layer plated from the comparative bath.
[0055] Example 2 Hull Cell Test Two aqueous nickel electroplating baths were prepared:
[0056] [Table 4]
[0057] [Table 5]
[0058] [Table 6]
[0059] The Hull Cell tests were conducted using the following operating parameters: applied current 5A, 3 minutes, 55°C, 4 LPM air agitation. Current density ranged from 2 ASD to 20 ASD along the length of the Hull Cell panel. During plating, the pH of the nickel bath in Table 4 was 4.26, and the pH of the nickel bath in Table 5 was 4.18. The pH of the nickel bath in Table 6 was 4.40. The Hull Cell panels were made of bronze (copper-zinc alloy). As in Example 1 above, the panels were first cleaned by electrocleaning and then activated with a pre-dip solution. After plating, the panels were rinsed with DI water and air-dried at room temperature. The thickness of each panel was measured by XRF as in Example 1 above. The thicknesses of the nickel deposits plated at 10 ASD from the nickel baths in Table 4 (invention), Table 5 (invention), and Table 6 (comparison) were 5.07 μm, 5.42 μm, and 5.79 μm, respectively.
[0060] Panels plated with the nickel bath of the present invention had a dull, matte appearance at current densities between 2 and 20 ASD. In contrast, panels plated with the comparative nickel bath had a haze at current densities below 10 ASD and appeared semi-bright at current densities between 10 and 20 ASD.
[0061] The roughness of the nickel layer of each panel was measured by an Olympus 3D Laser Microscope at 10 ASD points of the Hull Cell panel as described in Example 1 above. The surface roughness was characterized by an areal roughness index including Sa (arithmetic mean height) and Sdr (developed interfacial area ratio). The nickel layers plated from the baths in Table 4 had an average Sa of 0.086 μm and an average Sdr of 5.89%, while the nickel layers plated from the baths in Table 5 had an average Sa of 0.096 μm and an average Sdr of 6.31%. In contrast, the nickel layers plated from the comparative baths had an average Sa of 0.073 μm and an average Sdr of 2.47%. The nickel layers plated from the nickel plating baths of the present invention had significantly increased surface roughness compared to the nickel layers plated from the comparative baths.
[0062] Example 3 Beaker Test Several copper alloy C194 coupons were used with a plating area of 2.7 cm x 3 cm. C194 coupons are a type of semiconductor material used in the formation of lead frames. The C194 coupons were composed of copper (≧97%), iron (2.1-2.6%), phosphorus (0.015-0.15%), and zinc (0.05-0.2%). Each coupon was pretreated as in Example 1-2 above prior to nickel electroplating.
[0063] Three aqueous nickel electroplating baths were prepared:
[0064] [Table 7]
[0065] [Table 8]
[0066] [Table 9]
[0067] The temperature during electrolytic plating was maintained at 60°C, pH at 3.5, and the paddle travel distance and travel speed at 8cm x 30 cycles / min. The applied current density was set at 1, 5, 10, and 20ASD. The target nickel coating thickness was 0.75μm, but when the current density was 10ASD, some coupons had nickel coatings of 1.5μm or even 3.0μm. The coating thickness was tested by XRF. The coating roughness was measured by Olympus 3D Laser Microscope at points of 1, 5, 10, and 20ASD. The particle morphology was measured by SEM with Zeiss Sigma 300, 20KV, working distance 10cm.
[0068] The nickel plated coupons from baths that did not contain 5-mercapto-1H-tetrazole-1-methanesulfonic acid disodium salt or 5-mercapto-(1H)-tetrazolylacetic acid sodium salt were dull or semi-bright and had low roughness. In contrast, the nickel plated coupons from baths that contained 5-mercapto-1H-tetrazole-1-methanesulfonic acid disodium salt or 5-mercapto-(1H)-tetrazolylacetic acid sodium salt had matte coatings with significantly increased roughness. The average values of Sa and Sdr for the 0.75 μm thick nickel plated coupons are shown in Tables 10 and 11.
[0069] [Table 10]
[0070] [Table 11]
[0071] The average values of Sa and Sdr for coupons plated with nickel to thicknesses of 1.5 μm and 3 μm at 10 ASD are shown in Tables 12 and 13.
[0072] [Table 12]
[0073] [Table 13]
[0074] Example 4 Button shear test and wire bonding test A C194 copper alloy leadframe substrate measuring 6 mm by 27 mm was pretreated by electrocleaning and presoaking as described above in Example 1. The leadframe was electroplated from either the crude nickel bath of Table 2 in Example 1 or the comparative nickel bath of Table 14.
[0075] [Table 14]
[0076] Nickel electroplating was performed at 10 ASD for 30 seconds. The pH of the nickel plating baths was maintained at 3.5 during electroplating. The temperature of each bath was held at 60°C. A 0.75 μm nickel layer was deposited on the copper alloy of the lead frame. The thickness of the nickel layer was measured by XRF. The comparative nickel deposit had a morphology as shown in FIG. 1 and the coarse nickel deposit had a morphology as shown in FIG. 2. The particle morphology was characterized by SEM using a Zeiss Sigma 300, 20 KV, 10 cm working distance and 10,000x magnification. The nickel deposit in FIG. 2 shows the characteristic mound-like nickel deposit with protrusions from the nickel plating bath of the present invention. In contrast, FIG. 1 shows a substantially smoother nickel deposit characteristic of many conventional nickel baths.
[0077] The surface roughness of the nickel deposits was characterized by the areal roughness index Sa (arithmetic mean height) and Sdr (developed interface area ratio). The roughness of the coatings was measured by an Olympus 3D Laser Microscope. The nickel layer plated from the inventive bath had an average Sa of 0.106 μm and an average Sdr of 4.35%, while the nickel layer plated from the comparative bath had an average Sa of 0.095 μm and an average Sdr of 1.03%.
[0078] A palladium layer was then plated onto the nickel layer using a PALLADURE™ 200 palladium electroplating bath (available from DuPont de Nemours, Inc.) at 0.75 ASD for 3 seconds. The bath temperature was 45° C. The palladium layer on each nickel layer was 10 nm. A 3 nm thick gold layer was then plated onto the palladium layer using an AURALL™ 364 gold strike bath (available from DuPont de Nemours, Inc.). Gold plating was performed at 0.1 ASD for 15 seconds at 45° C. The PPF multilayer structure had layers of Ni 0.75 μm / Pd 10 nm / Au 3 nm.
[0079] The adhesive strength of the various nickel deposits was then tested by button shear testing. All coupons were then coated with molding compound EMC-G700LA (Sumikon bakelite Co.). To avoid unintended curing, the EMC was stored at -40°C and removed from the freezer 24 hours before the molding process. During the thawing process, the EMC was kept under vacuum to minimize moisture absorption. The molding compound was molded into buttons and cured at 175°C for 2 minutes in a conventional oven. The coupons with the button-shaped molding compound were then post-molded at 175°C for 4 hours. The coupons were cooled to room temperature. Half of the coupons with the button-shaped molding compound were exposed to moisture absorption resistance level-1, 85°C, and 85% relative humidity for 168 hours using an ESPEC benchtop temperature and humidity chamber, model SH-221. The coupons were placed in stainless steel baskets in the chamber and set at 85°C and 85% relative humidity for 168 hours (7 days). The coupons were then removed from the chamber and allowed to dry in ambient conditions.
[0080] All coupons were then subjected to button shear testing. The button shear testing conditions were as follows: a) Shearing device: Nordson Dage 4000 Multipurpose Bond Tester b) Cartridge: DS 100 c) Button height: 3mm d) Button diameter: 3~3.5mm e) Shear height: 20% of the button = 600μm f) Shear rate: 85 μm / sec g) Temperature: room temperature
[0081] The button shear test results for the comparative nickel PPF coupons and the crude nickel PPF coupons are shown in Table 15 below.
[0082] [Table 15]
[0083] The reduction in shear force for the crude nickel of the invention was significantly less than that for the comparative nickel. The crude nickel of the invention had improved adhesion over the comparative nickel.
[0084] A 25 μm diameter gold bonding wire (Heraeus AW-14) was solder bonded to the PPF surfaces of the comparative nickel and crude nickel described above using a K&S manual wire bonder model 4524. The adhesive strength of the various nickel deposits was then tested by wire pull strength and wire pull failure mode testing.
[0085] For wire pull testing, a Nordson Dage 4000 multipurpose bond tester was used (cartridge WP100, test speed 200 μm / sec). For wire pull and wire pull failure mode testing, the crack failure modes were stitch and neck breaks. The comparative nickel PPF had 84.6% neck breaks in failure mode and 15.4% stitch breaks in failure mode. In contrast, the crude nickel PPF had both neck and stitch breaks in failure mode of 50%. Wire pull and wire pull failure mode testing was performed in accordance with IPC-TM-650 Test Method Manual, Number 2.4.42.3, February 1998 (available from Originating Task Group MCM-L Substance Performance Task Group (D-33e)), The Institute for Interconnecting and Packaging Electronic Circuits, 2215 Sanders Road-Northbrook, IL 60062-6135). The results are shown in Table 16.
[0086] [Table 16]
[0087] Both neck and stitch fractures of rough nickel are industrially acceptable. Wire pull strength of rough nickel PPF was not significantly reduced. This was unexpected since a rough surface would be expected to reduce pull strength and gold wire would not be expected to adhere to a rough surface. Wire pull strength can be further optimized by adjusting the wire bonder and operating parameters.
Claims
1. Nickel ions and the formula: 【Chemistry 1】 (In the formula, R 1 is hydrogen, linear or branched (C 1 ~C 6 ) alkyl, linear or branched hydroxy (C 1 ~C 6 ) alkyl or their salts, linear or branched carboxy (C 1 ~C 6 ) alkyl or their salts, linear or branched sulfo (C 1 ~C 6 ) alkyl or their salts, linear or branched amino (C 1 ~C 6 ) alkyl, phenyl or benzyl, and X + H + 1. A nickel electroplating composition comprising a mercaptotetrazole having a cation group which is a cation of a metal ion selected from the group consisting of aryl, ... and aryl ions.
2. R 1 is hydrogen, linear or branched (C 1 ~C 6 ) alkyl, linear or branched hydroxy (C 1 ~C 6 ) alkyl or its salt, linear or branched carboxy (C 1 ~C 6 ) alkyl or its salt, linear or branched sulfo (C 1 ~C 6 ) alkyl or a salt thereof; X + But, H + , or Na + and K. + 2. The nickel electroplating composition of claim 1, wherein the alkali metal ion is selected from the group consisting of:
3. R 1 is hydrogen, linear or branched (C 1 ~C 3 ) alkyl, linear or branched hydroxy (C 1 ~C 3 ) alkyl or its salt, linear or branched carboxy (C 1 ~C 3 ) alkyl or its salt, linear or branched sulfo(C 1 ~C 3 ) alkyl or a salt thereof; X + But, H + , or Na + 2. The nickel electroplating composition of claim 1 ,
4. 2. The nickel electroplating composition of claim 1, wherein the mercaptotetrazole is selected from the group consisting of 5-mercapto-(1H)-tetrazolylacetic acid sodium salt, 5-mercapto-1H-tetrazole-1-methanesulfonic acid disodium salt, and mixtures thereof.
5. 2. The nickel electroplating composition of claim 1, wherein the mercaptotetrazole is in an amount of 5 ppm or greater.
6. The nickel electroplating composition of claim 5, wherein the mercaptotetrazole is in an amount of 10 ppm to 100 ppm.
7. 2. The nickel electroplating composition of claim 1, wherein the source of nickel ions is selected from the group consisting of nickel sulfate, nickel sulfate hexahydrate, nickel sulfate heptahydrate, nickel sulfamate, nickel sulfamate tetrahydrate, nickel chloride, nickel chloride hexahydrate, nickel carbonate, nickel methanesulfonate, nickel bromide, nickel fluoride, nickel iodide, nickel oxalate, nickel citrate, nickel tetrafluoroborate, nickel hypophosphite, nickel acetate, and mixtures thereof.
8. The nickel electroplating composition of claim 1 further comprising a source of chloride ions.
9. 9. The nickel electroplating composition of claim 8, wherein the source of chloride ions is selected from the group consisting of nickel chloride, nickel chloride hexahydrate, hydrogen chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, guanidine hydrochloride, ethylenediamine dihydrochloride, trimethylammonium chloride, pyridine hydrochloride, phenylammonium chloride, hydrazine dihydrochloride, and mixtures thereof.
10. The nickel electroplating composition of claim 1, wherein the nickel electroplating composition has a pH of 2-6.
11. The nickel electroplating composition of claim 1 further comprising a pH adjuster.
12. 12. The nickel electroplating composition of claim 11, wherein the pH adjuster is selected from the group consisting of sulfuric acid, hydrochloric acid, sulfamic acid, boric acid, acetic acid, aminoacetic acid, ascorbic acid, lactic acid, 5-sulfosalicylic acid, and salts thereof.
13. The nickel electroplating composition of claim 1 further comprising a surfactant.
14. 14. The nickel electroplating composition of claim 13, wherein the surfactant is selected from the group consisting of sodium di(1,3-dimethylbutyl)sulfosuccinate, sodium 2-ethylhexyl sulfate, sodium diamylsulfosuccinate, sodium lauryl sulfate, sodium lauryl ether sulfate, sodium dialkylsulfosuccinate and sodium dodecylbenzenesulfonate, perfluorinated quaternary amines and mixtures thereof.
15. 10. The nickel electroplating composition of claim 1, wherein the nickel electroplating composition is cyanide-free.
16. The nickel electroplating composition of claim 1 , wherein the nickel electroplating composition is free of alloying metals.
17. A method for electroplating nickel metal onto a substrate, comprising: a) providing the substrate; b) contacting the substrate with the nickel electroplating composition of claim 1; c) depositing a nickel layer on said substrate, said nickel layer having Sa≧70 nm and Sdr≧4%; The method includes:
Citation Information
Patent Citations
Anti-displacement hard gold composition
JP2011122236A
Acidic aqueous silver-nickel alloy electroplating composition and method
JP2021063291A
Packaging component and semiconductor package
US7190057B2
Lead frame for semiconductor package
US7285845B2
Release layer for metal foil with carrier, and metal foil comprising same
WO2022124843A1